The Influence of Job Stress Levels on Auditor Performance with Personality Traits of the Big Five Personality Model as Moderators - Widayani, Ni Luh Ulansari Manikan; Mimba, Ni Putu Sri Harta; Ratnadi, Ni Made Dwi; Dwija P, I Gusti Ayu Made Asri (Budapest International Research and Critics University, 2022)
State auditors have an important role in assessing whether public sector entities are doing what they are supposed to do and work to detect and prevent public corruption so that better management of nation finances can be achieved. Looking at several cases involving financial administrators, the big responsibility in realizing a clean and free nation from corruption, collusion and nepotism leads the auditor to a level of work stress which is estimated to affect the auditor's performance. This study examines the effect of work stress on auditor performance using the â€œBig Five Personality Traitsâ€ model which consists of five factors: extraversion, agreeableness, conscientiousness, openness to experience and neuroticism/emotional stability as moderating variables. The study is conducted by surveying 36 auditors who work for the Supreme Audit Board of the Republic of Indonesia representative in Bali Province (BPK RI Perwakilan Provinsi Bali) and using Partial Least Square (PLS) analysis. The result show that work stress level negatively affects auditor performance. The big five personality model also plays a role in moderating the effect of work stress on auditor performance with the following results: 1) openness to experience significantly strengthens the relationship between work stress level and auditor performance, 2) conscientiousness insignificantly strengthens the relationship between work stress level and auditor performance, 3) extraversion significantly weakens the relationship between work stress level and auditor performance, 4) agreeableness insignificantly weakens the relationship between work stress level and auditor performance and 5) emotional stability significantly weakens the relationship between work stress level and auditor performance.